THE EFFECT OF AUDITOR'S WORK EXPERIENCE, AUDITOR'S EXPERTISE AND EMOTIONAL INTELLIGENCE ON AUDITOR PERFORMANCE AT PUBLIC ACCOUNTING OFFICE IN SURABAYA - Regita Ardhiana Pratiwi; Arief Nurdiannova Qurochman (Jurnal Mantik, 2022)
The purpose of this study was to determine the effect of auditor's work experience, auditor's expertise and auditor's emotional intelligence on Auditor Performance. The sample used in this study was 32 respondents (auditors and auditor staff who worked at KAP in Surabaya for at least 3 years. The test used was multiple linear regression analysis technique. and the auditor's emotional intelligence has an effect on the auditor's performance, proven to be true.